2021
DOI: 10.1101/2021.12.09.471789
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipid droplets 3D full measurement by holographic in-flow tomography

Abstract: The most recent discoveries in the biochemical field are highlighting the increasingly important role of lipid droplets (LDs) in several regulatory mechanisms in living cells. LDs are dynamic organelles and therefore their complete characterization in terms of number, size, spatial positioning and relative distribution in the cell volume can shed light on the roles played by LDs. Until now, fluorescence microscopy and transmission electron microscopy are assessed as the gold standard methods for identifying LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…7E and F point out that LDs can be segmented even in the 3D RI tomogram reconstructed through the neural network. 69 Moreover, the SSIM between the two tomograms is very high (i.e., 0.996), thus confirming that the global content is preserved and only the fine details at the high frequencies are lost. Therefore, the 11.92% error in Fig.…”
Section: D Tomographic Imagingmentioning
confidence: 76%
“…7E and F point out that LDs can be segmented even in the 3D RI tomogram reconstructed through the neural network. 69 Moreover, the SSIM between the two tomograms is very high (i.e., 0.996), thus confirming that the global content is preserved and only the fine details at the high frequencies are lost. Therefore, the 11.92% error in Fig.…”
Section: D Tomographic Imagingmentioning
confidence: 76%
“…Moreover, the trend of changes in phase intensity was observed in line with the stiffness of cells characterized by AFM (Figure 7D); that is, softer cells exhibited relatively low phase values, corroborated by previous studies, 44 and plausibly rationalized by the phase being proportional to the sample thickness and inversely proportional to the refractive index. Furthermore, the refractive index may reflect how cells deformed along the axial direction, 45,46 and the biophysical parameters of cells, such as dry mass, wet mass, and protein concentration. Previous studies have observed a correlation between the cell refractive index and the protein concentration, 47,48 as well as the DNA content, for differentiating the G2/M phases from the G1/S phases.…”
Section: Phase Information Extracted By Qpdcmentioning
confidence: 99%
“…Low-coherence holotomography was used as a tool for long-term visualization and quantification of LDs in adipocytes [25]. A high-throughput comprehensive LDs visualization and characterization using a tomographic phase-contrast flow-cytometer was proposed by Pirone et al [26]. Here we used the CP-HHT system for novel highly sensitive measurements of LDs RI distribution and differentiation of the cholesterol-rich vs triacylglycerol (TAG)-rich LDs, which showcases the type of LDs predominant in the analyzed sample.…”
Section: Introductionmentioning
confidence: 99%
“…Low-coherence holotomography was used as a tool for long-term visualization and quantification of LDs in adipocytes 25 . A high-throughput comprehensive LDs visualization and characterization using a tomographic phase-contrast flow-cytometer was proposed by Pirone et al 26 .…”
Section: Introductionmentioning
confidence: 99%